Environmental Science - Botkin, Daniel B; Keller, Edward A (New Jersey : John Wiley, 2012)
Environmental Science: Earth as a Living Planet, Eighth Edition provides emphasis on the scientific process throughout the book gives readers the structure to develop their critical thinking skills.
Includes bibliographical references; Index I.1-I.9p.
Keywords: Biology; Environmental science